2020
DOI: 10.1111/jep.13351
|View full text |Cite
|
Sign up to set email alerts
|

Disseminating TF‐CBT: A Mixed Methods Investigation of Clinician Perspectives and the Impact of Training Format and Formalized Problem‐Solving Approaches on Implementation Outcomes

Abstract: Background: Trauma Focused-Cognitive Behavioural Therapy (TF-CBT) has been established as an evidence-based treatment for youth with traumatic stress symptoms. The versatility of TF-CBT in conjunction with its established effectiveness has led to its widespread dissemination. However, dissemination efforts have not always translated into sustainability, which has prompted a more thorough investigation into those factors that impact implementation and encouraged the development of strategies that promote sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…Third, TF-CBT includes the gradual exposure intervention activity that is common to effective PTSD treatments, directly targets and challenges negative and distorted thoughts and beliefs about the world, and provides coping skills education and practice. TF-CBT helps children regulate emotions surrounding a highly distressing stressor and enhance safety to prevent revictimization (Ascienzo et al, 2020; Morina et al, 2016; National Institute for Health and Care Excellence, 2018). Regulating emotions is important because maladaptive coping strategies, such as disordered eating or substance use, can come from a perceived lack of adaptive coping options.…”
Section: Treating Bullying With Trauma-focused Cognitive Behavioral T...mentioning
confidence: 99%
“…Third, TF-CBT includes the gradual exposure intervention activity that is common to effective PTSD treatments, directly targets and challenges negative and distorted thoughts and beliefs about the world, and provides coping skills education and practice. TF-CBT helps children regulate emotions surrounding a highly distressing stressor and enhance safety to prevent revictimization (Ascienzo et al, 2020; Morina et al, 2016; National Institute for Health and Care Excellence, 2018). Regulating emotions is important because maladaptive coping strategies, such as disordered eating or substance use, can come from a perceived lack of adaptive coping options.…”
Section: Treating Bullying With Trauma-focused Cognitive Behavioral T...mentioning
confidence: 99%
“…You could see she just didn't want to engage anymore. (Counsellor E) Anxiety about approaching traumatic memories is common both among traumatised youth in TF-CBT treatment (Neelakantan et al, 2019) and among counsellors who are delivering exposurebased trauma interventions (Ascienzo et al, 2020). In an abbreviated model of TF-CBT, the reduced time frame for completing the trauma narrative component may further reduce acceptability and tolerability of this component.…”
Section: Counsellor and Client Perceptions Of The Eight-session Tf-cb...mentioning
confidence: 99%
“…Research also indicates that many counsellors have concerns about implementing evidence-based treatments in general, and exposure-based PTSD treatments specifically, resulting in low fidelity to treatment protocols and reduced treatment effectiveness (Ascienzo et al, 2020). For example, a study of standard-length TF-CBT implementation in the United States found that only 66% of counsellors reported being likely to use all the treatment components (Allen & Johnson, 2015).…”
Section: Trauma-focused Cognitive Behavioural Therapymentioning
confidence: 99%
“…Much like other exposure-based intervention components, TNs are rarely used in practice. Studies examining therapists' perspectives of TF-CBT found that TNs were rated as one of the most difficult TF-CBT components to implement and considered to be only appropriate for some children [17,18]. One study found that, although all evidence-based protocols for trauma include some element of exposure, only 14-22% of trauma-exposed youth received exposure during treatment [8].…”
Section: Introductionmentioning
confidence: 99%